Patterns of women entrepreneurship: A qualitative study in Sri Lanka - Yogeswaran, T.; Grace, H.H.; Dilogini, K. (Monash University, 2019)
Entrepreneurship in Sri Lanka shows its great importance in socio-economic growth. Though it was dominated by males, it has now moved into a new trend where female starts new business ventures. Development of female entrepreneurs is a value-added point to the development and success of nations like Japan and Spain. But women entrepreneurs face many challenges, but motivational factors behind their own business encourage them to run this race. This study helped to discover the critical challenges, motivational factors and the optimal balance that could be drawn through these contrary factors. Data were collected by semi-structured, in-depth interviews with 25 women entrepreneurs from different sectors. Through the findings, a new model has been developed. This model depicts how the challenges and motivational factors meet at one point and finally lead to the entrepreneurial success which is the optimal balance of women entrepreneurs.
Keywords: Challenges; Entrepreneurship; Motivational factors; Women; Sri Lanka